2020
DOI: 10.34172/jhp.2020.42
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of the ethanol extract of Curcuma heyneana rhizome on isoniazid and rifampin-induced liver injury rats

Abstract: Introduction: Isoniazid (INH) and rifampin (RIF) are antituberculosis drugs that can induce injury in the liver. The purpose of this study was to investigate the antioxidant and hepatoprotective activities of the ethanol extract of Curcuma heyneana rhizome on liver injury in animal model induced by INH and RIF. Methods: Antioxidant activity was measured by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. All animals were divided into 7 groups. Liver injury was induced by using combination of INH at the dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Curcuma heyneana 6 Wistar Albino Rats Administration of ethanol extract of C. Heyneana rhizome at the dose of 25, 125 or 625 mg/kg significantly inhibited the elevated liver biomarkers. Treatment with doses of 125, 625mg /kg did not show any sign of necrosis.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Curcuma heyneana 6 Wistar Albino Rats Administration of ethanol extract of C. Heyneana rhizome at the dose of 25, 125 or 625 mg/kg significantly inhibited the elevated liver biomarkers. Treatment with doses of 125, 625mg /kg did not show any sign of necrosis.…”
Section: Resultsmentioning
confidence: 96%
“…INH along with RIF produces toxic metabolites or oxidants such as acetylhydrazine (AcHz) and hydrazine (Hz) which are oxidized by microsomal enzymes P450 especially CYP2E1 into radical metabolites. These metabolites cause hepatotoxicity 6 .…”
Section: Hepatotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…This plant grows easily in Indonesia. Research has shown that the C. heyneana extract was able to inhibit the increase of alanine transaminase (ALT) and aspartate transaminase (AST) induced by paracetamol as well as rifampin and isoniazid (4,5). However, the hepatoprotective activity of this extract toward ethanol induction has never been studied.…”
Section: Introductionmentioning
confidence: 99%